Brake Pedal Sizing and Preliminary Design of Balance Bar in the Brake of a SAE Formula Type Vehicle - Gomes, Lucas Olenski [UNESP]; Grandinetti, Francisco José [UNESP]; Martins, Marcelo Sampaio [UNESP]; Souza Soares, Alvaro Manoel [UNESP]; Reis De Faria Neto, Antônio [UNESP]; Castro, Thais Santos [UNESP]; Almeida, Luís Fernando (SAE International, 2024)
SummaryThe SAE Formula prototypes are developed by students, where in the competition, various aspects of project definitions are evaluated. Among the factors evaluated for scoring is the braking system, in which the present work aims to present the development and design of the braking system of a vehicle, prototype of Formula SAE student competition. As it is a project manufactured mostly by students, where the chassis, suspension system, electrical, transmission and powertrain are developed, it is important to first pass the static and safety tests, where the brakes of the four wheels are tested during deceleration at a certain distance from the track. To enable such approval and also to demonstrate, for the competition judges, the veracity of the system's sizing, all the parameters and assumptions of the choice of the vehicle's braking system are presented, thus ensuring their reliability, efficiency and safety. Using drawing and simulation software such as SolidWorks and Excel for calculation and income statement, it is possible to develop the project and clarify the method for any designer and evaluator. With the theoretical data obtained, it is possible to relate them with the data obtained by empirical tests, with the vehicle already built and in motion, in order to assertively validate the designed system and ensure its efficiency during the competition.